Factors Affecting Public Interest In Applying For Loans To Bank: Case Study on Furniture Entrepreneurs in Medan City - Lennaria Lusia Tarigan; Erni Dewi Munte; Bertha Nerpy Siahaan; Duma Lasmaria Siagian; Vikarma Jaya Halawa (Jurnal Ilmiah Manajemen Kesatuan, 2024)
In daily life, borrowing through financial institutions such as banks is a common activity. This study aims to examine the influence of perceived ease of use, perceived risk, privacy, trust, and perceived benefits on public interest in applying for bank loans. The study population consisted of 2,785 furniture entrepreneurs in Medan City, with 104 respondents selected through purposive sampling. Primary data were collected via questionnaires, supported by secondary data from relevant literature. Data analysis was conducted using Partial Least Squares (PLS) to assess relationships among variables. The findings reveal that perceived ease of use, privacy, trust, and perceived benefits significantly influence interest in borrowing from banks, while perceived risk does not show a significant effect. These results provide valuable insights for future research and contribute to the understanding of financial behavior, particularly in the context of entrepreneurial financing decisions. Keywords: perceived ease of use, risk, privacy, trust, perceived benefits, borrowing interest